Perkembangan Pendidikan Islam di Negara Eropa: Pendidikan Islam di Spanyol - Qurrata Akyuni (2022)
Islamic education in Spain began to develop, marked by the provision of the Spanish state religion department that schools in Spain were officially allowed to provide Islamic religious lessons for their Muslim students. This is due to the growing number of Muslim students in primary and secondary schools so that some areas in Spain have to offer Islamic religion classes. This official recognition from the government opens up opportunities for Muslims in Spain to teach religion in both public and private schools. In addition, there is also the opportunity to build self-managed schools, carry out worship and celebrate religious holidays.